Investigation of The Effect of Radiant Panel Positions and Water Temperature on Thermal Comfort - Oruc, Onur; Ozturk, Merve (GAZI UNIV, 2022)
Energy consumption and environmental pollution in the world are increasing day by day. For efficient use of energy, academicians and scientists have developed different models. One of these studies is high temperature cooling systems. Radiant panel systems are examples of high-temperature cooling systems with their performance. In this study, the effect of wall mounted and ceiling radiant cooling systems on thermal comfort is investigated numerically. Numerical results have been compared with the experimental data obtained from the literature and good agreement has been reached. The water temperature inside the radiant panels was defined as 20 degrees C, 22 degrees C and 24 degrees C, respectively and the results were compared according to the PMV (Predicted Mean Vote) - PPD (Predicted Percentage of Dissatisfied) parameters. Six different conditions were investigated and the results show that the best thermal comfort is provided by 20 degrees C of water temperature and the radiant ceiling condition.
Keywords: Thermal comfort; natural convection; PMV-PPD; radiant ceiling cooling; CFD; HEATING-SYSTEM; ENERGY-CONSUMPTION; COOLING SYSTEMS; FLOOR; PERFORMANCE; BUILDINGS; Engineering